(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Dengue fever, a mosquito-borne viral disease, imposes significant public health challenges globally, particularly in Bangladesh. It has been experiencing its most severe outbreak of dengue on record in 2023 and putting huge pressure on the health system. Objective: Tto investigate the demographic characteristics, clinical manifestations, laboratory findings in dengue patients. Methods: This observational study was conducted at tertiary level Kurmitola General Hospital, Dhaka over six months, involving 1000 patients diagnosed with dengue fever. Data on demographics, clinical symptoms and laboratory parameters were collected and analyzed. Results: The majority of participants were in the 21-30 age group (40%), Female (55%) predominance with 98% being Muslim and 85% residing in urban areas. All patients exhibited fever, with other common symptoms including vomiting (42%), loose motion (32%), and abdominal pain (27%). Laboratory findings showed significant thrombo- cytopenia and elevated liver enzymes, while renal function remained normal. Conclusion: The study highlights the prevalence of dengue fever among young urban population, with fever as a predominant symptom in patients with marked thrombo- cytopenia. These findings emphasize the need for a nuanced approach to assessing and managing dengue fever on the basis of clinical and laboratory findings. JAFMC Bangladesh, Vol 21, No 1 (June) 2025:32-35